THE IMPACT OF COVID-19 ON STUDENTS’ WILLINGNESS TO COMMUNICATE IN ENGLISH IN HIGHER EDUCATION INSTITUTIONS IN A DIGITAL CONTEXT (HEIs) - Anna Lynn Abu Bakar; Irma Wani Othman; Saifulazry Mokhtar; Sohaimi Mohd Esa (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The outbreak of the Covid-19 Pandemic has brought a shift in the way the teaching and learning process has been conducted in the education field. Most of the lessons are conducted in a digital context for the safety of both teachers and students. Thus, this study aims to look into the impact of the pandemic on studentsâ€™ willingness to communicate (WTC) in English in a digital context in a local higher education institution (HEIs) in Sabah, Malaysia. A qualitative approach was employed in this study involving 25 pre-university students. The data was obtained from a focus group interview and was later transcribed and coded into dominant and sub-dominant themes. The findings revealed that the students unanimously agreed that having classes in a digital context does affect their WTC in English. It is hoped that these findings would give a better insight to English language instructors (ELIs) to plan a conducive learning environment that could facilitate students’ WTC in a digital context.